Comparing strength and range of motion of the upper limb with AV fistula access with the contralateral upper limb among patients treated with hemodialysis - Hassabi, Mohammad; Poursaeidesfahani, Mehrshad; Khosravi, Shahrzad; Falaknazi, Kianoosh; Salehi, Shahin; Sadeghi Sowini, Roya; Javadi, Fatemeh; Abedi Yekta, Amir Hosein (Researcher Bulletin of Medical Sciences, 2018)
Introduction:The arteriovenous (AV) fistula is a gold standard method for safe and effective repeated vascular access for patients on hemodialysis (HD). The patients, with AV-fistula access in their upper limb, have some limitations in using the involved limb both in daily living and during the dialysis process. The aim of this study was to compare range of motion (ROM), muscle strength and arm circumference of fistula created limb with the contralateral upper limb. Material and Methods: 23 patients (50-85 year), receiving HD through AV fistula in one of their upper limbs, at least for 3 months, were enrolled. ROM, muscle strength, and arm circumference of both upper limbs were measured using goniometer, dynamometer and tape-measure, respectively. Then the values of the both sides were compared together. Results: In ROM tests shoulder forward flexion, backward extension, internal rotation, external rotation, horizontal extension, and horizontal adduction, and in muscle strength tests shoulder abduction and hand grip were significantly (p<0.05) more limited or weaker at the fistula side. Arm circumference was significantly greater at the fistula created limb. Conclusion: The upper limb, which is involved during HD process, is weaker and has more limited ROM in comparison with the contralateral limb. We suggest more attention to develop specific exercise programs for maintaining the abilities of the limb with AV-fistula access.